Assessing the Impact of Unfolding Case Study Scenarios during High-Fidelity Pediatric Simulation among Undergraduate Nursing Students - Allison C. Munn (MDPI AG, 2021)
Simulation helps to prepare prelicensure nursing students for practice by providing opportunities to perform clinical skills and make decisions in a safe environment. The integration of nursing knowledge, skills, and decision-making abilities during simulated unfolding case-study scenarios may enhance student self-confidence and foster clinical judgement skills. The purpose of this study was to assess the impact of simulation using unfolding case-study scenarios on undergraduate nursing students’ self-confidence in pediatric nursing knowledge, skills, and clinical judgment/decision-making abilities. This mixed methods study included a pre- and post-survey design to evaluate undergraduate nursing students’ confidence in pediatric nursing knowledge, skills, and decision-making abilities after participation in both an instructor-led (guided) and a student-led (decision-making) simulation involving unfolding case-study scenarios. Friedman’s ANOVA analyses revealed that all 16-items demonstrated statistically significant differences between the three measured responses (pre-simulation and both post-simulation surveys). Post-hoc Wilcoxon signed-rank tests revealed statistically significant differences in student ratings pre-simulation and post-instructor-led (guided) experience for all 16-scored items. The qualitative themes identified were perception of experience, pediatric nursing care, assimilation of knowledge, and critical thinking. Unfolding case-study simulation experiences positively impact the learning, self-confidence, and clinical judgement of undergraduate nursing students.